Notices of books. - Horrocks, Geoffrey (Journal of Hellenic Studies, 1997)
Reviews the book `Scripta minora ad linguam graecam pertinentia,' by C.J. Ruijgh, edited by J.M. Bremer, A. Rijksbaron and F.M.J. Waanders.